Pengaruh Content Marketing Instagram terhadap Potensi Leads Penjualan pada UMKM Kuliner - Nika, Syawla Ersi; Kasih, Jemiro; Shiroth, Salman Fathy (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
This study aims to examine whether Instagram-based content marketing strategies can increase the number of sales leads for UMKM RCFood. Instagram was chosen due to its interactive features, such as reels, stories, and bio links, which support content promotion. The study employs a quantitative correlational approach using a survey method and simple linear regression analysis. Data were collected via an online questionnaire in Google Forms, distributed to 100 followers of the Instagram account @rcfoodd, using purposive sampling. The results show that content marketing has a significant influence on lead volume, with a coefficient of determination (R²) of 0.591. One of the observed indicators was the increase in page views on Taplink, which was listed in the account’s bio, as well as direct messages from users, indicating their interest in proceeding to purchase. This implies that engaging and consistent content can drive user actions. Therefore, optimizing content strategies is recommended for MSMEs using social media to enhance customer engagement.